Major structural elements and appointment criteria to African Regional Courts with references to Treaty and protocol regulations : (as of January 2024) - Stroh, Alexander; Kisakye, Diana (2024)
Online Appendix to "Informality and Multi-level Judicial Appointment Processes in African Regional Courts" by Alexander Stroh and Diana Kisakye (2024)
Keywords: Appointment Rules; African REC courts